Chemical Biology Approaches toward Precise Structure Control of IgG‐Based Antibody‐Oligonucleotide Conjugates. (30th March 2023) - Shen, Lin; Wu, Yuanyuan; Xie, Wenxue; Chen, Guangyao; Xing, Hang
Abstract: Antibody‐oligonucleotide conjugates (AOCs) are important tools for drug development and biochemical analysis. However, the structural heterogeneity of AOCs synthesized through conventional coupling methods raises reproducibility and safety concerns in clinical trials. To address these issues, different covalent coupling approaches have been developed to synthesize AOCs with precise site‐specificity and degree of conjugation. This Concept article categorizes these approaches as linker‐free or linker‐mediated and provides details on their chemistry and potential applications. Several factors, including site‐specificity, conjugation control, accessibility, stability, and efficiency, are highlighted when evaluating the pros and cons of these approaches. The article also discusses the future of AOCs, including the development of better conjugation approaches to ensure stimuli‐responsive release and the application of high‐throughput methods to facilitate their development. Abstract : This Concept article is centered on different chemical biology approaches that enable the production of antibody‐oligonucleotide conjugates (AOCs) with accurate site‐specificity and degree of conjugation. These techniques are categorized into linker‐free or linker‐mediated conjugations, with an emphasis on the detailed chemistry and potential applications. Additionally, the article assesses the pros and cons of each method and provides a viewpoint on the future advancements in the field of precise AOCs.